Consider Common Management and Treatment Approaches to Control Legionella Bacteria. Issue 3 (5th March 2019) - Mofidi, Alexander; Lytle, Darren; Masters, Sheldon; Sidari, Frank; Krause, J. David
Abstract : Legionella is the leading cause of waterborne disease outbreaks in the United States. Fortunately, there are many ways to prevent or mitigate Legionella growth in premise plumbing systems.